Cell autocloning as a pathway to their real rejuvenation - Salnikov, Lev (Frontiers in Aging, 2024)
The article gives a brief description of geroprotection and rejuvenation methods known to date, presenting their main mechanisms and limitations. To overcome the main limitations of the process of rejuvenation, it is possible to use a process called “cell autocloning.” The principle of the proposed method of rejuvenation is as follows: a periodic process of autocloning of the cell nucleus is initiated in the cellular genome with the formation of one unstable daughter copy and its subsequent self-elimination. In this case, the process of cell division stops in the phase of nuclei divergence without subsequent physical separation of the cell itself. This is especially important for postmitotic cells, where the looping of the “unidirectional” line of the ontogenesis program into a “ring” will mean their transition into renewable cells. The prototype for autocloning mechanisms could be the already known ways in which cells adapt to the increasing amount of their damage over time. These are polyploidy and asymmetric cell division, relying on which it is possible to obtain a renewable process of cell nuclei division, when only the original nucleus remains as a result of division. Although this is not a simple task, there are possible pathways to its solution using approaches that can suggest modern knowledge from the field of molecular and cell biology and genetics. The realization of such a goal will require a lot of work, but the expected result justifies it.